HOW TO USE NONSTEROIDAL ANTI-INFLAMMATORY DRUGS AND THEIR EFFECTS ON THE BODY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are a class of drugs approved by the FDA for use as antipyretic, anti-inflammatory, and analgesic agents. These effects make NSAIDs useful for the treatment of muscle pain, dysmenorrhea, arthritic conditions, pyrexia, gout, migraines, and are used as opioid-sparing agents in some acute trauma situations.